MANAJEMEN PENGETAHUAN SISTEM PENILAIAN RAPORT PADA SEKOLAH SMP ISLAM TERPADU AR-RUDHO JAKARTA - Sugiyono Sugiyono; Achmad Noe'man (CKI ON SPOT, 2017)
Information that is built and maintained properly will provide the benefits of the use of information in a systematic and integrated by having an integrated arrangement. SMP  Islam Terpadu Ar-Rudho Jakarta organized a web-based student assessment report cards. In this regard the need for a way to insert data to build value into each component of the information environment in student scores. This is to facilitate the homeroom teacher to do the job to complete the task to enter the data value of students. With the information value of these students if it were made an application component integrated value for scan / enter data these values quickly and easily and also the provision of application given to the teacher to enter a value that will be treated by having uniformity components in the management of student scores were later will be submitted to the student's grade for inclusion in easily and quickly. From the discussion it will obtain student assessment facility by implementing an integrated component of the web-based values. This conclusion with ease in entering / enter the data.Keywords: Knowledge Management, UML, Web